Answer:
Step-by-step explanation:
If it's a riddle, then the answer is no time at all, simply because the field is already plowed.
Answer:
(4,3,2)
Step-by-step explanation:
We can solve this via matrices, so the equations given can be written in matrix form as:
Now I will shift rows to make my pivot point (top left) a 1 and so:
Next I will come up with algorithms that can cancel out numbers where R1 means row 1, R2 means row 2 and R3 means row three therefore,
-2R1+R2=R2 , -3R1+R3=R3
4R2+R1=R1 , -14R2+R3=R3
,
Therefore the solution to the system of equations are (x,y,z) = (4,3,2)
Note: If answer choices are given, plug them in and see if you get what is "equal to". Meaning plug in 4 for x, 3 for y and 2 for z in the first equation and you should get 20, second equation -10 and third 15.
The value of the expression in the form a(x+b)^2 is 1.5(x+2)^2 - 4
<h3>Vertex Form of a quadratic expression</h3>
Given the quadratic expressions
1.5x^2+6x+......
1.5(x^2 + 4x)
Using the completing the square method
The coefficient of x = 4
Half of the coefficient = 4/2 = 2
The square of the result = 2^2 = 4
The equation is expressed as:
f(x) = 1.5(x^2+4x+ 4) - 4
f(x) = 1.5(x+2)^2 - 4
Hence the value of the expression in the form a(x+b)^2 is 1.5(x+2)^2 - 4
Learn more on completing the square method here: brainly.com/question/1596209
Answer:
2x - 10
Step-by-step explanation:
2(x - 5)
distribute
2*x - 2*5
2x - 2*5
2x - 10
Answer:
5x - 2y = -2
Step-by-step explanation:
When subtracting one equation from the other, we are essentially just subtracting the left side of the second equation from the left side of the first equation and doing the same thing with the two right sides.
Here, we are subtracting (-7x + 3y) from (-2x + y):
(-2x + y) - (-7x + 3y)
Let's get rid of these parentheses. Remember that when we have a subtraction sign before a parentheses, we need to distribute a -1 to each term within those parentheses:
(-2x + y) - (-7x + 3y) = -2x + y + 7x - 3y = -2x + 7x + y - 3y = 5x - 2y
Now on the right side, we're subtracting 2 from 0:
0 - 2 = -2
Put it all together:
5x - 2y = -2
Hope this helps!